2001
DOI: 10.1063/1.1378309
|View full text |Cite
|
Sign up to set email alerts
|

Identification of refractory-metal-free C40 TiSi2 for low temperature C54 TiSi2 formation

Abstract: A refractory-metal-free C40 TiSi2 phase formed by pulsed-laser annealing is identified experimentally by combined convergent beam electron diffraction (CBED) study and CBED pattern simulation. The simulation shows that the C40 TiSi2 has a hexagonal structure with the space group P6222 (180) and lattice parameters a=0.471 nm and c=0.653 nm. Upon further furnace annealing or rapid thermal annealing, C54 TiSi2 can be directly achieved from C40 TiSi2 at low temperatures (600–700 °C). This observation suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…Figure 1͑b͒ ͑bottom spectrum͒ displays the Raman modes of the same as-laser-annealed sample. Compared with the previous results, 10,11 it is obvious that pure C40 TiSi 2 is the dominant phase after the laser annealing process in this work.…”
contrasting
confidence: 60%
See 2 more Smart Citations
“…Figure 1͑b͒ ͑bottom spectrum͒ displays the Raman modes of the same as-laser-annealed sample. Compared with the previous results, 10,11 it is obvious that pure C40 TiSi 2 is the dominant phase after the laser annealing process in this work.…”
contrasting
confidence: 60%
“…As a new TiSi 2 phase, the crystal structure of C40 TiSi 2 has been systematically investigated by high-resolution transmission electron microscopy ͑HRTEM͒, 11 and the direct phase transformation from the C40 phase to C54 phase was studied by Raman spectroscopy. 10,11 However, the pure C40-C54 transformation bypassing the C49 TiSi 2 phase has never been studied by x-ray diffraction ͑XRD͒, even the XRD pattern of the pure C40 phase resulting from the refractor-metalfree Ti/Si samples. In this work, we used x-ray diffraction to characterize C40 TiSi 2 directly formed by pulsed laser annealing a pure Ti/Si sample and the C40-C54 TiSi 2 phase transformation upon further RTP annealing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of this refractory-metal free laser induced C40 TiSi 2 was first identified using HRTEM by Chen et al 8 Recently Via et al 21 have also shown that by depositing a thin layer of Ta at the Ti/ Si interface, the C40 TiSi 2 was obtained after annealing at 525°C from their Bragg-Bentano XRD results. Both the refractory-metal free and the refractory-metal doped C40 TiSi 2 obtained by Li et al 9 and Via et al, 21 respectively, have shown that the C40 TiSi 2 has a hexagonal structure with the space group P6 2 22. 8.…”
Section: Resultsmentioning
confidence: 94%
“…The crystal structure of this C40 TiSi 2 had been studied using high resolution TEM ͑HRTEM͒ by Li et al 9 In this article, we report on the formation of C49 TiSi 2 at two different temperatures ͑i.e., 680 and 1975°C, respectively͒ when blanket Ti/ Si samples were annealed with a a͒ Electronic mail: scip1187@hotmail.com Nd:Yttrium-aluminum-garnet ͑YAG͒ laser with at 0.18 s and with an energy fluence of approximately 1.5 J / cm 2 . Moreover, additional refractory metal ion implantation causes integration issues.…”
Section: Introductionmentioning
confidence: 96%